The influence of friction stir welding tool shape on quality of AZ31 Magnesium welding product - Irza Sukmana; Fauzi Ibrahim; Ahmad Yudi Eka Risano (Universitas Muhammadiyah Metro, 2021)
Magnesium is one type of material that can be used as a base metal in welding. Magnesium has superior properties, including low density, good ductility, medium strength and excellent corrosion resistance. Because of its properties, the metal is widely used, ranging from household goods to aircraft components. These base metals are categorised as mild when viewed from the specific gravity of magnesium (1.74 g/cm3 and 1.83 g/cm3). Welding is the process of merging two or more base metals which are merged at the contact surface with or without additives or fillers. Welding is divided into two main categories, Liquid and Solid-State Welding. Friction Stir Welding (FSW) is an example of Solid-State Welding (Non-Fusion Welding). FSW is a friction welding process that twists the tool by utilising heat energy and pressing without additives or fillers until the base metal is in a phase change. The welding process in this study used the cone and spiral shape with a tool rotation at 2000 rpm and a welding speed of 16 mm/min. The tests carried out are tensile and hardness testing. This study found that the tool shape, tool rotation, and welding speed significantly affect the mechanical properties of the welded AZ31 magnesium. The spiral shape will make the welding area wider. Although the cone shape will have a small area, the weld will look perfect with good tensile strength, while the hardness values for the two tool shapes are almost the same, but the cone shape is better.